Photocatalytic Decolorization Study of Methyl Orange by TiO2–Chitosan Nanocomposites - Imelda Fajriati; Mudasir Mudasir; Endang Tri Wahyuni (Universitas Gadjah Mada, 2014)
The photocatalytic decolorization of methyl orange (MO) by TiO2-chitosan nanocomposite has been studied. This study was started by synthesizing TiO2-chitosan nanocomposites using sol-gel method with various concentrations of Titanium(IV) isopropoxide (TTIP) as the TiO2 precursor. The structure, surface morphology, thermal and optical property of TiO2-chitosan nanocomposite were characterized by X-ray diffraction (XRD), fourier transform infra red (FTIR) spectroscopy, scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and diffuse reflectance ultra violet (DRUV) spectroscopy. The photocatalytic activity of TiO2-chitosan nanocomposite was evaluated by photocatalytic decolorization of methyl orange as a model pollutant. The results indicate that the particle size of TiO2 increases with increasing ofthe concentration of TTIP, in which TiO2 with smallest particle size exhibit the highest photocatalytic activity. The highest photocatalytic decolorization was obtained at 5 h of contact time, initial concentration of MO at 20 ppm and at solution pH of 4. Using these conditions, over 90% of MO was able to be decolorized using 0.02 g of TiO2-chitosan nanocomposite under UV light irradiation. The TiO2-chitosan nanocomposite could be reused, which meant that the TiO2-chitosan nanocomposites can be developed as an effective and economical photocatalyst to decolorize or treat dye in wastewater.